Urbanization and development multidisciplinary perspectives - Beall, Jo, 1952-; Guha-Khasnobis, Basudeb; Kanbur, S. M. Ravi.; World Institute for Development Economics Research (Oxford : Oxford University Press, 2010)
This volume presents a collection that focuses on urbanization and its implications for economic development. Written for an advanced audience with an interest in urban economics and cities, the book contains case studies from India, Brazil, Tanzania, Lebanon, and South Africa.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Urbanization -- Economic aspects -- Developing countries